2020
DOI: 10.1002/ange.201913552
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Aromatic versus Induced Paratropicity: Synthesis and Interrogation of a Dihydro‐diazatrioxa[9]circulene with a Proton Placed Directly above the Central Ring

Abstract: We present a high‐yielding intramolecular oxidative coupling within a diazadioxa[10]helicene to give a dihydro‐diazatrioxa[9]circulene. This is the first [n]circulene containing more than eight ortho‐annulated rings (n>8). The single‐crystal X‐ray structure reveals a tight columnar packing, with a proton from a pendant naphthalene moiety centred directly above the central nine‐membered ring. This distinct environment induces a significant magnetic deshielding effect on that particular proton as determined by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…No dehydrogenation of 13 , to give 9 , was observed under these conditions. It should be noted that 13 contains the same circulene motif as that being presented in our previously reported dihydro-diazatrioxa[9]­circulene derivative . Dehydrogenation of 13 , to give the target [9]­circulene ( 9 ), was achieved quantitatively by treatment with DDQ.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…No dehydrogenation of 13 , to give 9 , was observed under these conditions. It should be noted that 13 contains the same circulene motif as that being presented in our previously reported dihydro-diazatrioxa[9]­circulene derivative . Dehydrogenation of 13 , to give the target [9]­circulene ( 9 ), was achieved quantitatively by treatment with DDQ.…”
mentioning
confidence: 62%
“…All individual aromatic rings constructing the circulenes have negative values, due to the diatropic ring current, and the central ring has positive NICS values due to the paratropic ring current. The presence of paratropic ring currents in the central nonaromatic rings of 9 and 10 can be explained by our previously reported concept of topologically induced paratropicity …”
mentioning
confidence: 63%
See 2 more Smart Citations
“…5 A large number of studies have shown that the degree of aromatic-city can be determined from magnetic shieldings, 6 ring-current strengths 7 and other molecular magnetic properties. [8][9][10][11] Electron delocalization and pathways of magnetically induced current densities provide information about molecular behaviour in the presence of an external magnetic field (B), which is important when designing novel magnetic materials. 12 The magnetic susceptibility (χ) also called magnetizability is a measure of interactions between matter and an external magnetic field (B).…”
Section: Introductionmentioning
confidence: 99%